SRC promotes lipogenesis: implications for obesity and breast cancer. (2nd January 2021) - Lin, Shu-Yong; Lin, Sheng-Cai
ABSTRACT: Remodeling of lipid metabolism has been implicated in cancers; however, it remains obscure how the lipid metabolic pathways are altered by oncogenic signaling to affect tumor development. We have recently shown that proto-oncogene tyrosine-protein kinase Src interacts with and phosphorylates the lipogenesis enzyme phosphatidate phosphatase LPIN1 to promote breast cancer development.